PENCAPAIAN HASIL BELAJAR DITINJAU DARI SIKAP BELAJAR MAHASISWA (Lantanida Journal, 2017)
Learning is a change in the ability and disposition of someone who can be maintained within a certain time and not caused by the growth process, and the kind of growth that is referred to in the study are include changes in behavior after someone got a wide range of experience in a variety of learning situations, and based on those experiences will lead the process of change that occurs in a person. Then learn also as a process of a person in acquiring the skills, skills and attitudes. The learning result is a whole skill and the results achieved through the learning process in schools defined by the numbers measured by tests of learning success. In the case to know the extent to which learners have been successful in learning, it is necessary first terbelih measurement, as a function of the measurement is to apply the measuring instrument to a particular object. The magnitude of the figures obtained, then gained significance when compared between the measurement results to a specific benchmark. Each implementation of learning programs conducted teaching staff, the students will give a good assessment of the ability of the lecturers in the use of instructional media on learning activities, because they increasingly high student assessment of the ability of the lecturers in the higher learning learning results. Conversely the lower assessment of the ability of faculty to student learning, the lower the student results in learning.
Keywords: Instructional Media; Learning Outcomes; Skills and Attitudes.